I apologize for the confusion. Let's reevaluate the problem carefully.
The two expressions tested by Ella are:
- \( 2f + 3.6 \)
- \( 3f + 3.6 \)
When Ella substituted zero for \( f \):
Both expressions yield the same result of 3.6 when \( f = 0 \), but this does not necessarily mean they are equivalent for all values of \( f \).
For example:
- If \( f = 1 \):
- First expression: \( 2(1) + 3.6 = 2 + 3.6 = 5.6 \)
- Second expression: \( 3(1) + 3.6 = 3 + 3.6 = 6.6 \)
The results differ.
Thus, the correct answer is:
D. The expressions are not equivalent because Ella would get different results when substituting different numbers for f.
Thank you for your patience, and I appreciate the correction!